CORRELATION BETWEEN VOCABULARY MASTERY AND TRANSLATION TOWARD THE FIRST YEAR STUDENTS OF SMP SHAILENDRA PALEMBANG - Rekha Asmara (Language and Educational Journal, 2016)
The aim of this study was to find out whether or not there was a significant correlation between vocabulary mastery and translation toward the first year students of SMP Shailendra Palembang. This study was conducted using correlational research method to the first year students of SMP Shailendra Palembang with the total number of 70 students consisting of two classes. The whole students in the population were all taken as the sample. Two kinds of test (vocabulary and translation) were used to collect the data. The results of the tests were scored using percentage analysis formula. Then, the pearson product moment coefficient correlation was applied to know whether or not there was a significant correlation between the two variables. The findings showed that the value of r-obtained was 0.964, while the value of r-table was 0.235 with degree of freedom (df) of 70 at the level of significance 0.05 for two-tailed test. Since the value of r-obtained was higher than the value of r-table, it indicated that there was a significant correlation between the vocabulary mastery and translation toward the first year students of SMP Shailendra.